The Design of DC Micro Grid with a Load-Based Battery Discharge Method for Remote Island Electrification Utilizes Marine Currents and Solar Photovoltaic - Faanzir; Mochamad Ashari; Soedibyo; Suwito; Umar (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
This paper presents the design of DC micro grid with a load-based battery discharge method for remote island electrification utilising marine currents and solar photovoltaic. To anticipate the intermittent, a load-based battery discharge method is proposed. A centralized battery storage is sized according to the unfilled load demand by the marine current and the solar PV. Thus, the length of the turbine diameter is varied to meet the optimum system size. Hourly data of marine current speed from Cipalulu Strait in Maluku, Indonesia is provided. Data at a typical time, shows that the marine current peak power occurs every 6 hours perday, whereas the PV is at noon. The loads divide into 6 categories, including household 1, household 2, villagse office, school, mosque, and public health center with the peak demand as 112 kW and 856 kWh perday. All loads, mainly for lightings and electronic equipment work in 24 V DC through converters. The distribution network employs 320 V DC connecting from the power plan to the community residents. Simulations demonstrate that the battery size, solar PV, and turbine radius matches to meet the loads. Simulations also show that the battery utilization meets its current and capacity, meaning that an optimum size and filling the load profile can be smoothly conducted.